Global Health Emergencies During the Pandemic and Their Solutions - Sencan, Irfan; Bulut, Dilek; Agalar, Canan; Sencan, Ismail Hakki (Tubitak Scientific & Technological Research Council Turkey, 2021)
Abstract: In this review, we evaluated health care problems, which were not common before pandemic outbreak but have been common issues after its appereance and approaches to control pandemic considering its influences on people. We revised current health care developing approaches under the light of experience obtained throughout the pandemic so far. The aim is to be prepared in advance for possible upcoming pandemics. As in Covid 19 pandemics, such long lasting and widely affecting situations, durability is also very important together with flexibility and quickness. To provide durability, we need global policies taking the health to its center as well as health system policies.Key words: Covid-19, health system, emergency, crisis, vulnerability, durability
Sencan, Irfan/0000-0003-0465-5090; Sencan, Ismail Hakki/0000-0002-9200-6025
Keywords: Halk Ve Çevre Sağlığı; Sağlık Politikaları Ve Hizmetleri; Covid-19; Emergency; Vulnerability; Crisis; Health System; Durability